Kontribusi Guru Pak Dalam Membentuk Karakter Remaja Usia 11-14 Tahun Diera Digital - Susiana Lase; Ferdi Eka Darma; Sandra R. Tapilaha (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This research aims to explore how teachers of Christian Religious Education (PAK) contribute to shaping the character of adolescents aged 11-14 in the context of the digital era. Based on the findings of this article, there are several fundamental issues, including adolescents who are addicted to online games while watching inappropriate video content. Through understanding these core issues, this writing aims to provide education and enlightenment through the teaching of Christian Religious Education. Using a qualitative study method and phenomenological approach, data were collected through in-depth interviews with Christian Religious Education (PAK) teachers experienced in teaching adolescents in the digital era. Therefore, it is hoped that Christian Religious Education teachers will diligently carry out their duties in accordance with the goals of education and learning, namely to shape and produce generations with good morality, responsibility, and exhibit characters in line with Christ's teachings. Additionally, the emotional relationship between teachers and students is also recognized as an important factor in shaping adolescent character. These findings provide better understanding for educators and policymakers about the importance of the teacher's role in addressing the challenges of character formation in the digital age.